The architectural office Vladimir Šterk in the period 1923-1941 - Kahle, Darko (Array, 2018)
The article reconsiders the oeuvre of Architect Vladimir Šterk through his own Architectural Office and parallel joined office with Architect Jovan Korka in the period 1932-36. A thorough examination of circa 600 folders from various archives reveals 181 signed or attributed projects and realizations. Possibly, at least further 400 items were in some manner products made by employees or collaborators of Architectural Offices he effective controlled.